2006
DOI: 10.1590/s0004-28032006000400005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional status of nonhospitalized patients with liver cirrhosis

Abstract: -Background -Protein-calorie malnutrition is a frequent fi nding in patients with chronic liver disease, but investigations of nutritional status have been rarely performed in individuals seen at outpatient clinics. Aim -To evaluate the nutritional status of patients with alcoholic and nonalcoholic cirrhosis, attended for the fi rst time at a reference outpatient clinic for liver diseases. Patients and methods -A total of 300 consecutive patients attended at the outpatient clinics of a reference center for liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
107
0
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 34 publications
8
107
0
12
Order By: Relevance
“…Most clinical studies about malnutrition in alcoholics do not separate subjects with visceral disease from those without, or consequences of simply reduced energy intake from more specific alcohol effects (8) . Few classic studies have been updated, references in modern surveys about protein-calorie and vitamin deficits often being 10-20 years old (15,21) .…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical studies about malnutrition in alcoholics do not separate subjects with visceral disease from those without, or consequences of simply reduced energy intake from more specific alcohol effects (8) . Few classic studies have been updated, references in modern surveys about protein-calorie and vitamin deficits often being 10-20 years old (15,21) .…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition also has important implications in liver transplantation and it has been demonstrated that patients with a worse nutritional status before the transplant have increased postoperative complications and higher mortality rates. 5 In a study on 300 patients, Carvalho et al 6 showed that more than 55% of those with advanced hepatic disease had some degree of malnutrition, which was moderate to severe in 40%. In the same study, 95% of Child-Pugh class C patients were malnourished, as also were 74% of class B and 46% of class A patients.…”
mentioning
confidence: 99%
“…In the same study, 95% of Child-Pugh class C patients were malnourished, as also were 74% of class B and 46% of class A patients. 6 The high prevalence of malnutrition even in patients in the early stages of the disease is a source of concern. Among the causes of malnutrition in these patients, particularly important are insufficient food intake, malabsorption and metabolic disorders.…”
mentioning
confidence: 99%
“…(106) Apesar do crescimento atual da CH por VHC, a doença hepática de etiologia alcoólica ainda encontra-se bastante presente na prática clínica e em algumas instâncias estando superior a decorrente do VHC. Em concordância com outros estudos (20,107,108) , a prevalência da etiologia alcoólica neste estudo foi elevada. O predomínio da etiologia por álcool pode estar relacionado ao predomínio do sexo masculino na amostra estudada.…”
Section: Discussionunclassified
“…Esta depleção no tecido muscular pode estar relacionada ao efeito direto do álcool sobre o metabolismo do músculo esquelético. (32,93) Carvalho & Parise (2006) (107) (114) . A relação da etiologia com a gravidade pode estar associada à maior prevalência de ascite, encefalopatia hepática e HDA neste grupo de pacientes.…”
Section: Discussionunclassified